Religion, Tradition, and Modernization: Portrait of the Shift in Dawuhan Tradition in the Ngerso Community, Tawangmangu Karanganyar - Nabilla, Hawa La'ala; Mibtadin, Mibtadin; Farhah, Eva; Talib, Kartini Aboo (Balai Penelitian dan Pengembangan Agama Semarang, 2024)
This study explains the transformation of the Dawuhan Tradition in Ngerso, Tawangmanggu, which is influenced by changes in religious practices that develop in the local community. This study uses a Cultural Studies approach to analyze changes in symbols and rituals that occur in the ceremony. The theory chosen in this study is Derrida's deconstruction theory, which is determined to reveal and understand the layers of meaning behind cultural and religious transformations. The main objective of this study is to show how negotiations between local traditions and religious influences reshape the implementation of the Dawuhan Tradition. Descriptive and qualitative methods collect data through in-depth interviews, observations, and documentation. The results of this study indicate that there are changes in the implementation of the Dawuhan Ceremony, such as changes in the time of implementation, replacement of sacred elements, and changes in offerings presented to ancestors. These changes are a reflection of the cultural negotiations that occur between local traditions and religious influences. This negotiation is carried out to maintain the relevance of the ritual in the context of modern life. In conclusion, this study provides an overview of the complex socio-cultural dynamics in society (religion and culture); tradition must adapt to social change without losing its essence. This research implies that it is a form of preserving tradition in changing times, which is done by reinterpreting it to be more relevant. On the other hand, this research also shows the existence of social and political hegemony over changes in tradition, and it can be underlined that the flexibility and ambiguity of Javanese tradition allow society to negotiate and adapt to change without losing its cultural identity.